DNA methylations of MC4R and HNF4α are associated with increased triglyceride levels in cord blood of preterm infants. Issue 35 (August 2016) - Kwon, Eun Jin; Lee, Hye Ah; You, Young-Ah; Park, Hyesook; Cho, Su Jin; Ha, Eun Hee; Kim, Young Ju
Abstract : Abstract: The association of preterm birth with obesity and metabolic syndrome later in life is well established. Although the biological mechanism for this association is poorly understood, epigenetic alterations of metabolic-related genes in early life may have important roles in metabolic dysfunction. Thus, we investigated the associations of DNA methylations of melanocortin 4 receptor (MC4R) and hepatocyte nuclear factor 4 alpha (HNF4α) with metabolic profiles in cord blood of term and preterm infants. We measured metabolic profiles in cord blood samples of 85 term and 85 preterm infants. DNA methylation and mRNA expression levels of MC4R and HNF4 α in cord blood cells were quantified using pyrosequencing and real-time PCR. Triglyceride (TG) levels were grouped by percentile as low (<10th percentile), mid (11th–89th percentiles), and high (>90th percentile). A multiple linear regression model was used to assess the differential effects of DNA methylation on metabolic indices in cord blood between term and preterm infants. The beta-coefficients for associations between TG levels and methylation statuses of MC4R -CpG3 and HNF4α- CpG2 in the P1 promoter differed significantly between term and preterm infants ( P = 0.04 and P = 0.003, respectively). DNA methylation statuses of MC4R -CpG3 and HNF4α –CpG2 in the P1 promoter were significantly lower in preterm infants in the high-TG group compared with those in the mid- and low-TG groups ( P = 0.01). Notably, preterm infants in the high-TG group had higher TG levels in cord blood than term infants in the high-TG group (60.49 vs 54.57 mg/dL). In addition, MC4R and HNF4α expression levels were higher in preterm infants than in term infants ( P < 0.05). Epigenetic alterations of the newly identified genes MC4R and HNF4α in early life might contribute to metabolic profile changes, especially increased TG levels, in the cord blood of preterm infants. Abstract : Supplemental Digital Content is available in the text